Marketing Transformation of Halal Enterprises via Social Media: An Analytical Study of Muslim Millennials - Aulyatu Rachmadhani Hakim; Nanang Setiawan; Thorida Nur Asih (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
This study aims to analyze the influence of digital platforms on the growth of halal businesses among Muslim millennials, with a particular focus on the role of Islamic lifestyle and sharia-based brand identity. The research employs a qualitative approach through a literature review to explore current conditions, emerging trends, and challenges within the digital halal ecosystem. The findings indicate that social media plays a vital role in disseminating information, raising awareness, and promoting halal products. Nevertheless, the level of halal awareness among Muslim youth still requires enhancement through more systematic educational strategies. Theoretically, this study contributes to the growing body of literature on digital halal marketing in the context of the millennial generation. Its practical contribution lies in offering strategic recommendations for business practitioners to leverage social media in reaching the young Muslim market segment. The novelty of this research lies in the integration of Islamic identity, digital behavior, and sharia-compliant branding strategies within the contemporary halal business landscape